2020
DOI: 10.1007/s12178-020-09608-0
|View full text |Cite
|
Sign up to set email alerts
|

Dry Needling as a Treatment Modality for Tendinopathy: a Narrative Review

Abstract: Purpose of Review Tendinopathy describes a combination of pain, swelling, and impaired performance of the tendon and around structures. There are various treatment options for tendinopathy with unclear efficacy. Dry needling involves inserting needles into the affected tendon, and it is thought to disrupt the chronic degenerative process and encourage localized bleeding and fibroblastic proliferation. The purpose of this review is to review the use of dry needling as a treatment modality for tendinopathy. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Several conventional interventions have been used for tendinopathy and are found to be non-reflective to address any destruction to the healthy tissues. Several conventional interventions such as eccentric muscle strengthening, iontophoresis, ultrasound, phonophoresis, low-level laser treatment, and extracorporeal shockwave therapy have been advocated for the treatment of patellar tendinopathy (54). The effectiveness of different conventional interventions appears to be unproven for the treatment of patellar tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several conventional interventions have been used for tendinopathy and are found to be non-reflective to address any destruction to the healthy tissues. Several conventional interventions such as eccentric muscle strengthening, iontophoresis, ultrasound, phonophoresis, low-level laser treatment, and extracorporeal shockwave therapy have been advocated for the treatment of patellar tendinopathy (54). The effectiveness of different conventional interventions appears to be unproven for the treatment of patellar tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it has been reported that ultrasonography guided treatments facilitate the development of percutaneous procedures of regenerative healing in tendinopathy (55). The efficacy of DN under the guidance of sonography has been evaluated in several reported studies and found to be statistically significant for the treatment of tendinopathy, rotator cuff, and tendons around the greater trochanter (54). Hence, it is demonstrated that this technique can be adopted and utilized as a first-line therapy or as a secondary treatment for the treatment of tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis is that dry needling could stimulate a healing response. Repeated passages of the needle would produce physical trauma to the tendon which induces bleeding and in turn releases growth factors that stimulate a healing response [ 80 ]. Another hypothesis is that passages of the needle could change a chronic tendon injury into an acute inflammatory state leading to the formation of granulation tissue.…”
Section: Ultrasound-guided Procedures Without Injectionmentioning
confidence: 99%
“…This leads to alterations to the length and tension of the selected muscle fibers, which further activate nearby mechanoreceptors 71,73 . In previous studies, authors have suggested that dry needling is most effective when a local twitch response is elicited 70 . In addition, in several studies, authors have suggested that dry needling increases local blood flow through the release of vasoactive substances such as calcitonin gene-related peptide (CGRP) and Substance P, which provide downstream vasodilatory effects 70,72 .…”
Section: Dry Needlingmentioning
confidence: 99%
“…To date, most investigations of dry needling have focused on the rotator cuff, patellar tendon, and lateral epicondyle as tissue targets 70 . In 2020, a narrative review of the available literature on dry needling and tendinopathy noted general improvement in patient-reported symptoms with limited complications and low morbidity in most studies 70 . With regard to hamstring tendinopathy specifically, case reports have been published showing significant improvements in pain and self-reported outcomes that were sustained 6 months after the intervention 72 .…”
Section: Dry Needlingmentioning
confidence: 99%